Peran Faktor Psikologis Dalam Proses Pembelajaran: Membangun Kesuksesan Di Dunia Pendidikan - Abdul Farid; Nurfarida Deliani; Juliana Batubara (JOURNAL SAINS STUDENT RESEARCH, 2024)
This article aims to find out the Role of Psychological Factors in the Learning Process: Building Success in Education. the research conducted in this article is field research using a descriptive qualitative approach. The results showed that Building Success in the World of Education first Self-Efficacy as a Driver of Learning Motivation, Emotional Intelligence to Improve Social Interaction, Psychological Well-Being as a Positive Mental Foundation, Contribution to Improving the Quality of Education if these psychological aspects have run optimally, of course it leads to success in the world of education.